Chemical Characteristics of Non-Dairy Cheese from Coconut Milk as an Alternative Ingredient for Lactose Intolerance - Halim, Judella Kusuma; Hidayah, Nurul; Juwitaningtyas, Titisari; Mutmainah, Mutmainah; Fitriani, Aprilia (Universitas Ahmad Dahlan, 2023)
Lactose-intolerant people are unable to ingest cheese since it includes lactose. Lactose-free cheese can be made using coconut milk as an alternative. Coconut milk can substitute milk as a raw material for cheese production because it is rich in proteins such as albumin, globulin, prolamin, and glutelin. This research aims to determine how different proportions of coconut milk and soy extract affect the nutritional value of coconut milk cheese. Cheeses with 80:20, 70:30, and 60:40 ratios of coconut milk to soy extract are made by directly acidifying soy extract with lemon juice. Protein, lipid, and moisture content were all evaluated. At compositions 80:20, 70:30, and 60:40, the protein content of coconut milk cheese was 3.85%; 4.80%; and 5.73%, respectively. Coconut milk cheese had lipid contents of 28%, 27%, and 25.74%, respectively; the moisture contents were 64.93%; 61.92%; and 60.49%. This research contributes to utilizing coconut milk as a milk substitute.